Kegiatan Maghrib Mengaji untuk Meningkatkan Akhlak & Pengetahuan Agama Anak-anak Jorong Batang Gunung Pasaman Barat - Rahmadani Rahmadani; Marlian Arif Nasution; Rabiatul Adawiyah; Timbul Surya Akbar Lubis; Diana Rizky Lubis; Zakiyah Rangkuti; Salsabila Hasibuan; Sholatiah Hannum; Ahmad Mulyadi; Mar’ie Muhammad (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
This service aims to find out the Maghrib Koran Recitation Activities in Jorong Batang Gunung, Nagari Koto Gunung Ujung Gading, Lembah Melintang District, West Pasaman Regency. This service uses a qualitative approach to gain an in-depth understanding of the implementation of Maghrib Koran activities carried out by STAIN Madina KKN students in Jorong Batang Gunung, Nagari KotoGunung Ujung Gading, Lembah Melintang District, West Pasaman Regency. Data was collected through interviews, observation and documentation. Data analysis was carried out descriptively by grouping information based on themes that emerged from interviews and observations. The Maghrib Koran activity carried out by STAIN Madina KKN students in Jorong Batang Gunung, Nagari Koto Sawah, Lembah Melintang District, West Pasaman Regency, has had a significant impact on society, especially the younger generation. The positive impact of the Maghrib Koran activity can also be seen from the changes in participants' attitudes after participating in this program. Many of them began to show a deeper interest in religious activities and attempted to apply the values learned in their daily lives. Overall, this Maghrib Koran activity provides a strong foundation for the development of religious education in the area.